Inner Radiation Belt Simulations During the Successive Geomagnetic Storm Event of February 2022 - Kirolosse M. Girgis; Tohru Hada; Akimasa Yoshikawa; Shuichi Matsukiyo; Abraham C.‐L. Chian; Ezequiel Echer (Space Weather)
Abstract Starting from 29 January 2022, a series of solar eruptions triggered a moderate geomagnetic storm on 3 February 2022, followed subsequently by another. Despite the typically minimal impact of unintense storms on space technology, 38 out of the 49 Starlink satellites underwent orbital decay, re‐entering Earth's atmosphere. These satellite losses were attributed to enhanced atmospheric drag conditions. This study employs numerical simulations, utilizing our test particle simulation code, to investigate the dynamics of the inner radiation belt during the two magnetic storms. Our analysis reveals an increase in proton density and fluxes during the transition from the recovery phase of the first storm to the initial phase of the second, primarily driven by intense solar wind dynamic pressure. Additionally, we assess Single Event Upset (SEU) rates, which exhibit a 50% increase in comparison to initial quiet conditions.